2007
DOI: 10.1002/lt.21322
|View full text |Cite
|
Sign up to set email alerts
|

Retransplantation for hepatitis C: Results of a U.S. multicenter retransplant study

Abstract: It is widely perceived that outcomes are relatively poor following retransplantation (reTX) for recurrent of hepatitis C virus (HCV) infection. Transplant centers debate the utility of offering another liver to these patients. A U.S. study group was formed to retrospectively compare survival after reTX in patients with recurrent HCV (histologically proven) and those transplanted for other indications greater than 90 days after first transplantation, from 1996 to 2004. Patients were divided into 3 groups; group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 33 publications
4
69
0
1
Order By: Relevance
“…Such was the case in only 2 of the patients for whom a gap (2.5 and 4.7 years) was found between a biopsy with a fibrosis stage less than or equal to 4 and cirrhosis. For the other 15 patients, the median time between biopsies was 9 months (range, [5][6][7][8][9][10][11][12][13][14][15][16][17][18], in which the fibrosis progressed by a median of 3 stages (range, 1-6). For those who presented decompensation, the length of time from LT to cirrhosis was 2.5 years (range, 4 months to 8 years), and the number of completed biopsies was 3.4.…”
Section: Patients With Decompensated Cirrhosis At Baseline (N ϭ 17)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such was the case in only 2 of the patients for whom a gap (2.5 and 4.7 years) was found between a biopsy with a fibrosis stage less than or equal to 4 and cirrhosis. For the other 15 patients, the median time between biopsies was 9 months (range, [5][6][7][8][9][10][11][12][13][14][15][16][17][18], in which the fibrosis progressed by a median of 3 stages (range, 1-6). For those who presented decompensation, the length of time from LT to cirrhosis was 2.5 years (range, 4 months to 8 years), and the number of completed biopsies was 3.4.…”
Section: Patients With Decompensated Cirrhosis At Baseline (N ϭ 17)mentioning
confidence: 99%
“…15 Graft failure and cirrhosis from progressive HCV appear to be the reasons for the decrease in survival after LT. 15 Recently, the results of a multicenter study for retransplantation for HCV graft cirrhosis suggested that retransplantation may be an option in well-selected patients. 16 As this clinical story develops and treatment options for HCV after LT expand, prognostic factors for decompensation and survival will be critically important for determining the optimal timing of retransplantation for HCV. To answer these questions, a retrospective analysis was performed from an LT database that spanned 16 years at the University of Florida.…”
mentioning
confidence: 99%
“…22,23 However, these studies also demonstrate that HCV is more difficult to clear post-LT once advanced fibrosis and cirrhosis have developed, and re-transplant outcomes for recurrent HCV remain poor. 24 Our study has limitations inherent to a single center such as relatively small sample size and center specific histological interpretation. However, the availability of serial histologic data and the granularity of clinical data allow us to draw conclusions about donor and recipient interactions that would not be possible from a large database analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Este daño hepático se atribuye a un daño citopático directo del virus sobre el hepatocito 15,20,21 . La eficacia del tratamiento combinado con interferón pegilado y ribavirina es aún menor que en el resto de los enfermos con recurrencia de hepatitis C. Aunque esta complicación es infrecuente, cuando se evalúan los pacientes que necesitan retrasplante por recurrencia de la hepatitis C, el 19% es debido a una hepatitis colestásica fibrosante de la hepatitis C 22 . Desafortunadamente, un porcentaje importante de aquellos retrasplantados vuelven a presentar una hepatitis colestásica con un curso rápido a la descompensación hepática.…”
Section: Hepatitis Viral Cunclassified